Examining the Impact of Product, Price, and Service Priorities on Customer Satisfaction in Digital Journal Publishing: An AHP and Pearson Correlation Approach - Lestari, Putri Ayu; Eddyono, Fauziah (Yayasan Sinergi Kawula Muda, 2025)
The digital transformation of the scientific publishing industry has reshaped customer expectations regarding service quality, pricing, and product innovation. Yet, limited empirical insights exist into how these dimensions collectively shape customer satisfaction within digital publishing environments. This study identifies and prioritizes the key factors driving customer satisfaction in digital scientific journal publishing at PT Penerbit Ilmiah Indonesia. A quantitative design integrating the Analytical Hierarchy Process (AHP) and Pearson correlation analysis was employed to evaluate the priorities and interrelationships among product, price, and service quality dimensions. Data were obtained from 106 Open Journal Systems (OJS) users through an online survey encompassing 12 evaluation sub-criteria. The AHP results revealed interface design (0.1986), system reliability (0.1544), and review process speed (0.1201) as top priorities. Pearson correlation results demonstrated that price showed the strongest association with satisfaction (r = 0.846, p < 0.001), followed by service quality (r = 0.814) and product quality (r = 0.715). These findings underscore the strategic need to enhance platform usability and ensure pricing transparency to foster user satisfaction and loyalty. The study contributes to advancing data-driven service optimization frameworks and provides actionable insights for publishers to refine customer-centric digital marketing strategies.